PENGARUH KEGIATAN EKTRAKURIKULER MUHADHARAH TERHADAP KARAKTER RELIGIUS PERSERTA DIDIK KELAS XII DI MADRASAH ALIYAHYASTI SEKURA TAHUN PELAJARAN 2022/2023 - Nadia Nadia; Eliyah Eliyah; Sera Yuliantini (CV. ADIBA AISHA AMIRA, 2024)
This study aims to clearly describe: First. How are the extracurricular muhadharah activities at Madrasah Aliyah Yasti Sekura, second, how is the religious character of class XII students at Madrasah Aliyah Yasti Sekura, third is there a significant influence between extracurricular muhadharah activities on improving the religious character of class XII students at Madrasah Aliyah Yasti Sekura in the 2022/2023 academic year. This study uses a quantitative method with a survey research type. Data collection techniques use indirect communication techniques and observation. The data analysis techniques used are percentage, central tendency and simple linear regression. The results of the study concluded that: How are the extracurricular muhadharah activities at Madrasah Aliyah Yasti, namely: First, requiring all students to take part in extracurricular Muhadharah activities. Second All students get a turn to present a lecture or sermon. How is the religious character of class XII students at Madrasah Aliyah Yasti Sekura, namely: First, students are required to pray Zuhur and Asr in congregation until it becomes a habit for students to carry out their obligations as Muslims, second, students have good ethics. Is there a significant influence between muhadharah extracurricular activities on improving the religious character of class XII students at Madrasah Aliyah Yasti Sekura, there is a significant influence between muhadharah extracurricular activities and religious character at MA Yasti Sekura. The R square value = 0.151 or 15.1% is the contribution of muhadharah extracurricular activities to religious character values, while the remaining 84.9% is influenced by other factors, which are explained by other variables not examined in this study.